2018
DOI: 10.1016/j.cherd.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of a biomass CHP plant in UK: The Heathrow energy centre case

Abstract: Bioenergy has an important role to play in helping the UK meet its carbon target in 2050 and the European Renewable Energy Directive objectives for 2030. There are however uncertainties associated with the use of bioenergy, and whether or how much it contributes to greenhouse gas emission reductions. In order to help identifying environmental benefits and burdens associated with biomass use for energy production, an attributional life cycle assessment has been carried out of a biomass-fired CHP plant: the Heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Biomass feedstock can be used to produce steam or heat for the generation of electricity or other useful bio-fuel such as bio-methane, bio-ethanol, bio-diesel, and biomass pellets [2], [55]. Biomass has already found application in combined heat and power (CHP) for both small and large scale purposes [56]- [62]. The use of biomass for energy production depends on factors related to emission coefficient, technology efficiency, resource accessibility, land use/ownership policies, social acceptance, and costs.…”
Section: A Biomassmentioning
confidence: 99%
“…Biomass feedstock can be used to produce steam or heat for the generation of electricity or other useful bio-fuel such as bio-methane, bio-ethanol, bio-diesel, and biomass pellets [2], [55]. Biomass has already found application in combined heat and power (CHP) for both small and large scale purposes [56]- [62]. The use of biomass for energy production depends on factors related to emission coefficient, technology efficiency, resource accessibility, land use/ownership policies, social acceptance, and costs.…”
Section: A Biomassmentioning
confidence: 99%
“…Tagliaferri et al analyzed and evaluated the life cycle of biomass cogeneration power plants in the UK through a case study. The results show that the use of biomass can reduce greenhouse gas emissions [32]. Hailong Li et al analyzed the factors that affect the efficiency of biomass cogeneration, and found that flue gas quenching (FgQ) plays an important role in combined heat and power (CHP) plants based on biomass or waste.…”
Section: Cogeneration System and Biomass Cogenerationmentioning
confidence: 99%
“…The countries that fully utilize biomass energy sources are Brazil, the United States, and India (Schill, 2013). In the United Kingdom, one of the main biomass initiatives is the implementation of a combined heat power plant with a 10 MW capacity at Heathrow Airport, helping the airport meet its goal of reducing carbon emissions by 34% (Tagliaferri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%